Analisis Peranan Pemilahan Dalam Pengelolaan Sampah Untuk Menjaga Lingkungan - Umi Wasilatur Rohmah; Lutfiyatul Fahmi; Esafani Auraningtyas; Nur Ngazizah (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study examines the important role of waste sorting in waste bank operations for environmental preservation purposes. This analysis highlights the importance of effective waste segregation practices in facilitating sustainable waste management. This research uses a qualitative descriptive approach using observation and interview methods. The results obtained from this research are an in-depth understanding of waste management regarding waste sorting based on type.